The Basis Of The Judge's Consideration In Deciding The Rejection Of The Marriage Isbat Application Against The Position Of The Child In The Gorontalo Religious Court - Rivandi Ohihiya (Universitas Negeri Gorontalo, 2019)
This research aims to find out the basis of the judge's consideration in deciding the rejection of the marriage isbat application against the position of the child in the Gorontalo Religious Court, and to know the legal consequences of the rejection of the marriage isbat against the position of the child in the Gorontalo Religious Court. The research method used is empirical legal research with a data results approach on the ground. The results of the study showed the basis of the judge's consideration to reject the marriage application because the husband still has a marriage bond with his first wife, based on the provisions of Article 3 Paragraph 1 where a husband can only have a wife and vice versa, and also in article 9 of the Marriage Law where a married husband cannot marry again unless he has obtained the consent of the first wife or parties concerned. And as a result of the law their marriage is in the eyes of the law is not legal and their child only has a civil relationship with the mother and family of the mother because it is considered as a child of out-of-wedlock results.